2005
DOI: 10.1081/ddc-54315
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, in Vitro and in Vivo Evaluation of Liposomal/Niosomal Gel Delivery Systems for Clotrimazole

Abstract: Clotrimazole, which is an imidazole derivative antifungal agent, was widely used for the treatment of mycotic infections of the genitourinary tract. To develop alternative formulation for the vaginal administration of clotrimazole to provide sustained and controlled release of appropriate drug for local vaginal therapy, liposomes/niosomes were evaluated as delivery vehicles. To optimize the preparation of liposomes/niosomes with regard to size and entrapment efficiency, multilamellar liposomes/niosomes contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Secondly, niosomes may help localize the drug at the site of infection, in the vicinity of the infective fungus leading to increased efficacy. This is because the entrapment of a drug in vesicles improves solubility and helps in the localized delivery and deposition at the site of action (Ning, Guo, Pan, Chen, & Gu, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, niosomes may help localize the drug at the site of infection, in the vicinity of the infective fungus leading to increased efficacy. This is because the entrapment of a drug in vesicles improves solubility and helps in the localized delivery and deposition at the site of action (Ning, Guo, Pan, Chen, & Gu, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Fnz, itraconazole and ketoconazole have been proven to be active against Candida species [4]. Ketoconazole and clotrimazole (as liposomal/niosomal proliposomes) have been reported to be significantly therapeutically effective when given in solutions [21,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Limited stability in aqueous formulations represents one of their major drawbacks [154]. Concerning the treatment of vaginal infections, several works have been done studying liposomes for the formulation of antifungals [154,[172][173][174] and antibacterials [172,175] …”
Section: Several Authors Used Mucoadhesive Polymers Such As Eudragit®mentioning
confidence: 99%
“…Liposomal based bioadhesive and thermogelling systems have been further studied in vitro as final dosage forms for some of these liposomes. For instance, research groups working independently showed that the inclusion of different drug-loaded liposomes (based on egg phospholipids), in a Carbopol® 974P bioadhesive gel improved liposome stability in a media simulating the vaginal environment (37ºC; simulated vaginal fluid with pH 4.2) while delaying the release of clotrimazole[174,176] and metronidazole[176]. Ning et al further tested multilamellar vesicles, both liposomes and niosomes (which are vesicles similar to liposomes and prepared with non-ionic surfactants, in this case Span®40) in an oophorectomized female rat Candida infection model[174].…”
mentioning
confidence: 99%
See 1 more Smart Citation